Exploring the Attitudes and Perceptions of Master of Medical Education Graduates Towards Research Publication in Saudi Arabia - Alabdulqader,Noof A; Al-Nasser,Sami; Masud,Nazish (Advances in Medical Education and Practice, 2022)
Noof A Alabdulqader,1– 3 Sami Al-Nasser,2,3 Nazish Masud2,3 1Department of Medicine, Ministry of Health, Dammam, Saudi Arabia; 2Department of Medical Education, College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riaydh, Saudi Arabia; 3King Abdullah International Medical Research Center, Riyadh, Saudi ArabiaCorrespondence: Noof A Alabdulqader, Tel +966554993690, Email 413231001@ksau-hs.edu.saIntroduction: Evidence is lacking to identify what encourages students to conduct research and publish. This study aimed to understand the barriers and facilitators of research and publications from Master of Medical Education student research projects as 15– 20% have published their research while 75– 80% did not.Methods: This study used qualitative in-depth interviews with 17 graduates from the previous 13 batches of the Master of Medical Education program, Saudi Arabia. In-depth interviews were conducted with participants by face to face and Zoom, using a semi-structured interview guide. The interviews were conducted in English, and the recordings were transcribed verbatim. Next, the interview text was read multiple times to familiarize with the data for thematic analysis, where the text was coded inductively. Themes were generated by identifying patterns in the data and merging similar codes. The data were interpreted within the themes and supported with the most relevant quotations.Results: We identified four distinct but interrelated themes and the first theme, the importance and advantages of conducting research and its publication, explains the participants need to conduct research and publish it to survive and progress in the academic environment. In the second theme, positive experiences of conducting research and its publication, we identify what participants’ positive experiences of the research process entail. In the third theme, challenges to conducting research and its publication, we explore the participants’ opinions on the barriers to their efforts to undertake and publish ...